Is the Outcome the Most Important Modulator of Rating of Perceived Exertion in Male and Female Badminton Players? - Jiménez, Manuel; Torres-Luque, Gema; Fernández-García, Jose; Alvero-Cruz, José Ramón (Science and racket sports V, 2021)
Measures such as blood lactate (Bla), mean heart rate (mHR:) and ratings of perceived exertion (RPE) have been used as an index of physical effort in racket sports. The present study estimated the relationship between RPE and outcome in a sample of thirty-five single badminton players (fifteen women) from the Spanish National Clubs League (mean +/- SD) : age 22. 67 years +/- 4. 35 years and 22.70 years +/- 5. 55 years; weight 58. 92 kg 4. 90 kg and 71. 96 kg +/- 2.42 kg; Height 1.65 m +/- 2.05 m and 1.79 m +/- 0.68 m; and BMI 21.58 kg/m(2) 2.05 kg/m(2) and 22. 39 kg/m(2) +/- 1. 41 kg/m(2), for females and males respectively). Results showed no differences in mHR and Bla after winning or losing their games. Nonetheless, the RPE showed a significant outcome dependence [females t(13) = 4. 489, p < 0. 017 and males t(18) =2. 580, p <0. 019]. Pearson's correlation coefficients showed positive correlations between HR and Bla (r = 0. 48, p <0. 01) and Bla and RPE (r =0. 45, p <0. 05), as was expected. In conclusion, RPE could be strongly influenced by the outcome, suggesting that not only physiological, but also psychological aspects such defeat frustration or victory euphoria and could be an important RPE modulators to be considered to study the winner effect in sports.
Keywords: physical effort; badminton; RPE; winner effect; WOS(2)